The Iconography of Digital Windows—Perspectives on the Pervasive Impact of the Zoom Digital Window on Embodied Creative Practice in 2020. Issue 1 (5th March 2021) - Neideck, Jeremy; Pike, Shane; Kelly, Kathryn; Henry, Kat
Abstract : A window has traditionally been a sturdy artistic metaphor, able to offer a tangible account of acts of witnessing and perception. For many theatre directors and teachers, the window of our eyes has become our primary creative and pedagogical tool, gazing within the edifice of Zoom, a technology built by the intersection of interlocking digital windows, their meaning created by the witnessing gaze of the participants. And what are the windows of Zoom revealing? In the context of shared and embodied creative practice, we gain insight into other people's worlds: bodies on the move, negotiating shared spaces, attending to human need. Insight over Zoom is knowledge of the other without inter-subjectivity. The subtle voyeurism inherent in the technology offers often uncomfortably intimate access to the personal or domestic world of students and colleagues, but a window that does not readily lend itself to social connection or reciprocal or mutual gaze. We have seen things now that we cannot unsee. What will come of the digital heterotopia of the window when we venture back into the studio, when our performance making practices once again move about freely in the world? Have we all been rehearsing a new, interconnected futurity—a permanently alternate ordering of the actual world? Drawing from the practice of four teacher-artists (director, actor trainer, devisor, and dramaturg) this article will explore the iconography of the Zoom window, and its specific qualities at the intersection of body and technology.